TRADISI MEMBACA AL-QUR’AN SETIAP PRA KEGIATAN DI PC PEMUDA PERSIS SUMEDANG - Rijal Fadilah (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Nowadays, the Quran is not just a reading and meditation, but the Quran has been implemented in various forms according to the understanding they take from the Koran, as well as what has become a tradition in the Sumedang area, especially the North Sumedang area. In this research the author used direct field immersion and phenomenology methods to obtain comprehensive data. In the data obtained, the aim is that people reading the Quran before the activity is something positive because reading the Quran makes the heart feel calmer and also brings optimism within oneself that events filled with goodness will make it easier and smoother. In Islamic tradition, this is something that is worth preserving because it could be that the time spent is the last time of life, to anticipate this, how great it would be before starting the event to have the reading of the holy verses of the Koran with the hope that what will be heard at the end of life will be the Quran.